Regulasi Hukum Terhadap Keterlibatan Korban Tindak Pidana Penyelundupan Manusia - Hana Farah Dhiba; Sabinadevi Sabinadevi (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2021)
This study aims to analyze the legal regulation of victims who are involved in the occurrence of people smuggling by looking at the forms of participation and the relationship between the perpetrator and the victim. The method used in this research is a qualitative descriptive method with a normative legal approach. The research was conducted by collecting facts of events in the field and analyzing them on the basis of the applicable laws and regulations. The results of the study conclude that victims of criminal acts of human smuggling can be subjects to legal proceedings. That is due to the human smuggling offenses or passive assistance with the severity of which is in accordance with the form and extent of their actions in realizing the crime.